#TITLE_ALTERNATIVE# - DESRIANTI (NIM 10104072), WIDIA
Surface treatment of components of an airplane is a chemical process to ensure its strength and durability. This thesis discusses the scheduling problem of the surface treatment production process. The problem will be modeled as an optimization model, in which its objective is to minimize the finishing time. The model is one of an NP-hard job-shop scheduling. The solution of this model is the optimal schedule, which is shown in a Gantt chart. From the solution we can determine the efficiency that can be obtained if we use the optimal schedule. In this thesis we also discuss the sensitivity analysis of the parameters that are involved in the model.